Perception of the Non-English Department Students toward the Use of Artificial Intelligence in English Language Writing Activities - Desti Ariani; Riza Eka Putri; Ade Dwi Jayanti (LPPM Politeknik Raflesia, 2026)
The rapid advancement of Artificial Intelligence (AI), especially generative AI applications such as ChatGPT, Grammarly, Google Tanslate, or Quillbot, has significantly influenced every aspect of educational practices. In English language learning class, especially for Non-English Department students, Artificial Intelligence has widespread used to help the students deal with their English inadequacy competence whether speaking, reading, and even writing. This study aims to investigate Non-English Department students’ perception toward the use of AI in writing activities. The research focuses on how students view the benefits and challenges related to AI enhanced writing. A qualitative descriptive approach was employed through questionnaires and interviews involving 28 students. The findings indicate that most students perceive AI positively because it helps in expanding vocabulary, enhancing grammar, generating ideas, and improving writing efficiency. However, students also raise concerns regarding the challenges related to lack of competence, limited access, inaccuracy information, and plagiarism issue in using AI. The study concludes that AI can be a supportive tool in writing activities if used responsibly and ethically under proper academic guidance